Isolasi dan Karakterisasi Bakteri Penghasil Enzim β-CGTase dari Tanah Perkebunan Ubi Jalar - Kurniadi, Helman; Sagita, Desi; Hartesi, Barmi; Andriani, Lili; Dahlia, Dimbi (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
β-CGTase (β-cyclodextrin glycosyl transferase) is an enzyme that converts starch into CD (cyclodextrin). The CD is a high-value oligosaccharide used for modifying food, textiles, chemicals, medicines, cosmetics, and biotechnology. This research aims to obtain isolates of β-CGTase producing bacteria from sweet potato plantation soil. Screening is carried out using Horikoshi media which contains the color indicators phenolphthalein and methyl orange. Bacteria producing β-CGTase will give a yellow hollow zone if they grow on this media. CGTase activity was measured using a UV-Vis spectrophotometer. Three isolates producing CGTase were obtained, coded BSP6A, BSP6B, and BSP6C, which had the characteristics of being Gram-positive, shaped like bacilli, produced spores, were motile, had a positive catalase test, and could ferment acid. These three isolates were able to produce the optimum CGTase enzyme if incubated for 18 and 24 hours at a temperature of 37°C and pH 10 and were able to convert starch into CD if incubated for 30 minutes at a temperature of 37°C and pH 7.